ANALISIS PENDAPATAN USAHA TANI TEMBAKAU DI DESA SUKAWATI KECAMATAN SUKAWATI KABUPATEN GIANYAR - Gordianus Amal; Putu Fajar Kartika Lestari; Ni Putu Sukanteri (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2022)
Tobacco farming in Sukawati Village, Sukawati Subdistrict, Gianyar Regency community has managed well, sehigga will get high production results. The hope of farmers in producing agricultural production to get maximum crop yields. The purpose of the study is to find out the income of tobacco farming in Sukawati village of Sukawati District of Gianyar Regency. The research was conducted in Sukawati Village, Sukawati District, Gianyar Regency. The selection of the location is done intentionally (Purposive). Quantitative data includes land area, amount of production, income, receipts, while qualitative data includes data on the state of farming business in Sukawati Village, Sukawati District of Gianyar Regency. The variables involved in this research include: Farm business output, variable input cost, total acceptance, profit or profit. The data sources used in this research are primary data and secondary data. The research population is farmers who work on people's tobacco farming businesses in subak juwuk, Sukawati Village, Sukawati Subdistrict, Gianyar Regency. Where the tobacco growing season is only once a year, namely May, and the harvest is July to August, almost all farmers work on tobacco crops, namely tobacco and for local consumption, the yield is 6-7 klongkong per land area of 28 acres. The results of the study showed that the age of the characteristics of tobacco farmers in Sukawati Village and their experience in tobacco farming, the characteristics of these farmers can be seen from several aspects that include the age of farmers, education level, number of family members, average farmland area of 28 acres. Tobacco farming that harvests tobacco every 1 time in one season and the system on average harvesting can last for 6 months, thus one season of tobacco farming is approximately three to three months, the average quantity of tobacco production in one season reaches 225 kg with a price of Rp 50,000 / kg, the acceptance of tobacco farming on the area of arable land per one plant season is Rp 11,250,000, The average income of tobacco farmers amounted to 7.940.000 Rp, per average land area of 28 acres in one growing season. Keywords: Revenue, Revenue, cost, efficiency